Spectrum of TP53 Mutations in BRCA1/2 Associated High-Grade Serous Ovarian Cancer - Boyarskikh, Ulyana A.; Gulyaeva, L. F.; Avdalyan, A. M.; Kechin, A. A.; Khrapov, E. A.; Lazareva, D. G.; Kushlinskii, N. E.; Melkonyan, A.; Arakelyan, A.; Filipenko, Maxim Leonidovich (Frontiers in Oncology, 2020)
Objective: Mutations in TP53 lead to loss of function or gain of function (GOF) of the corresponding protein, p53, and have a different effect on the tumor. We aimed to determine the spectrum of TP53 mutations in BRCA1/2 associated serous ovarian cancer (HGSOC). Methods: The study population comprised of HGSOCs with mutations in BRCA1 (78) or BRCA2 (21). Only chemo-naive and platinum-sensitive patients were included in this study. The case group of the IARC database (n = 1249) with HGSOC not stratified by BRCA status was used as a reference. A custom NGS panel was used for sequencing TP53 and mutation hot-spots of other genes, p53 expression was evaluated by immunohistochemistry for 68 cases of HGSOCs. Results: TP53 mutation (95) or inhibition of wild-type p53 expression (3) was observed in 98 cases. The sample with normal p53 had CDKNA1 mutations. The frequency of truncating mutations was significantly higher than in the reference cohort (30.3% vs 21.0%, p = 0.01). Most of the samples (41/68) demonstrated low (or absent) expression of p53 and 17 samples overexpressed p53. LOH was typical for TP53 nonsense mutations (14/15). In total, 68/95 samples were LOH positive and showed LOH in all tumorous cells thus indicates the driver effect of TP53 mutations. Three specimens had KRAS, BAX, APC, and CTNNB1 subclones mutations. Conclusion: High frequency of truncating mutations, the low expression of mutant p53, and the lack of oncogenes mutations indicate the low manifestation of the potential GOF properties of p53 in BRCA1/2 associated HGSOC.